A review on microfabrication of thermoplastic polymer‐based microneedle arrays - Juster, Herwig; Aar, Bart; Brouwer, Hans (Polymer engineering and science, 2019)
This article will provide an overview of recent developments for microneedles made using injection molding and hot embossing techniques for active transdermal drug delivery. Microneedle arrays are developed for pain‐free and efficient drug delivery without using a cold chain. The focus of this article will be on the use of engineering thermoplastics and microneedle manufacturing techniques including patterning. Recent developments demonstrate that commercialization of polymer‐based microneedle systems is feasible. POLYM. ENG. SCI., 59:877–890, 2019. © 2019 Society of Plastics Engineers